2007
DOI: 10.1016/j.msea.2007.02.119
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and mechanical properties of high power laser surface-treated metallic glasses

Abstract: The processing power of high power Nd:YAG laser has been utilised to achieve the inherently high cooling rates required to form many of today's bulk metallic glasses (BMGs). The production of thick (≥250 m) amorphous surface layers has been considered. Microstructural and chemical observation techniques including scanning electron microscopy (SEM) and transmission electron microscopy (both with energy-dispersive X-ray spectrometry, EDS), and X-ray diffraction (XRD), reveal that fully amorphous layers are attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…[8][9][10][11][12] Due to rapid heating and cooling, lasers have been widely used to welding, cutting, cladding, alloying, glazing, annealing, melting, or ablating the small-scaled amorphous alloys such as ribbons, films, and wires, [13][14][15][16][17] very recently extending to BMGs. 18,19 Through laser-processing, microstructures, 15-17 magnetic properties, 14 forming ability, 20 and mechanical properties 19 of this kind of glassy alloys can be significantly improved, whereas only few works have focused on the surface patterns. 13,21,22 Its underlying physics is still unclear and deserves further investigations.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Due to rapid heating and cooling, lasers have been widely used to welding, cutting, cladding, alloying, glazing, annealing, melting, or ablating the small-scaled amorphous alloys such as ribbons, films, and wires, [13][14][15][16][17] very recently extending to BMGs. 18,19 Through laser-processing, microstructures, 15-17 magnetic properties, 14 forming ability, 20 and mechanical properties 19 of this kind of glassy alloys can be significantly improved, whereas only few works have focused on the surface patterns. 13,21,22 Its underlying physics is still unclear and deserves further investigations.…”
mentioning
confidence: 99%
“…It was also observed that, as the wear continues, the asperities of the shear bands break down, resulting in accumulation and compaction of micro-and nano-scale debris behind the shear bands. While the amorphous alloys showed a lower coefficient of friction, the wear rates were comparable to the steel specimens [15]. Prakash investigated abrasive two-body wear of Fe-, Co-, and Ni-based amorphous alloys and reported extensive micro-cutting and micro-cracking of the amorphous alloys [9].…”
Section: Introductionmentioning
confidence: 96%
“…As amorphous alloys lack general ductility, the wear behavior of these materials is characterized by shear banding and microcracking in the contact region [9,14,15]. Matthews et al investigated the dry sliding wear behavior of as-cast and laser remelted Cu-based amorphous alloys and observed formation of shear bands inclined to the sliding direction [15]. It was also observed that, as the wear continues, the asperities of the shear bands break down, resulting in accumulation and compaction of micro-and nano-scale debris behind the shear bands.…”
Section: Introductionmentioning
confidence: 99%
“…Laser processing techniques such as laser cladding and laser remelting have been utilized in producing various amorphous coatings. 9,10) In the last several years, studies have focused on the use of compositions based on (Fe, Ni, Co)-B-Si-Nb alloy systems. These compositions are mostly suitable for surface coatings on traditional steel substrates.…”
Section: Introductionmentioning
confidence: 99%